Pemberdayaan Kepemimpinan Perempuan dalam Program Studi: Studi Kasus Universitas Swasta di Samarinda - Brantasari, Mahkamah; Ananta, Aris; Anggraeni, Ayu; Warman, Warman (Academy of Education Journal, 2024)
Women's leadership in study programs can also provide inspiration and motivation for other women to pursue academic and leadership careers. This can help increase accessibility to educational and professional opportunities for women. This method involves an in-depth analysis of eight study programs led by women at one of the Private Universities (PTS) in the city of Samarinda. Researchers can examine how women's leadership influences organizational culture, policies, and study program outcomes. So a case study was carried out in an effort to obtain data related to leadership in eight study programs led by women. Role models that encourage inspiration, female leadership can be powerful role models for students and staff, especially for women, in demonstrating that a successful academic career is achievable for everyone regardless of gender. By inspiring and providing support, female leadership motivates study program members to reach their best potential and contribute to collective success. Women's leadership influences organizational culture, policies and study program outcomes. Women's leadership at private universities in the city of Samarinda not only has a positive impact on the progress and development of study programs, but also strengthens the values of inclusivity, empathy and equality in the academic environment, creating wider opportunities for mutual growth and success.